Exchange Rate Uncertainty and Optimal Participation in International Trade - Mundaca, Gabriela (2012)
Instead of just focusing on the effect of exchange rate levels (undervalued or overvalued exchange rates) on trade, this paper provides an analysis of the effects of exchange rate volatility levels on international trade. Intuitively, an increase in exchange rate volatility leads to uncertainty for agents participating in international trade, and such uncertainty might have a negative impact on international trade flows and participation, thereby reducing the advantages of world-wide specialization. This is especially crucial for countries where exchange rate derivatives markets are not yet well developed and the costs of hedging exchange rate risk are very high. The model here considers optimal decisions about participation in international trade under uncertainty about the exchange rate. The main conclusion is that a high level of exchange rate volatility can deter entrepreneurs from becoming exporters, even though exporting can be highly profitable. For those already participating in international trade, it is opposite: they may, optimally, choose not to leave the market even though staying in this market is highly unprofitable in the short run.